10 - Latchkey Experiences of School-Age Children in Low-income Families in Akwa Ibom State, Nigeria - Ekot, Mildred (Africa Development, 2021)
The study investigated the Latchkey experiences of school-age children (5-13 years) from the perspectives of mothers in low-income families in Uyo, Akwa Ibom State, Nigeria. A proportionate stratified random sample of 200 was drawn from high density areas of the five strata making up the study area. Data collected were analysed using frequencies, percentages and means and revealed the latchkey arrangement common in the area including, hiding the house key at the backyard or other places for children to gain entrance to the house after school, dropping the key in a neighbour’s house or shop, opening the house door through a window, while only two per cent reported giving duplicate keys to their children to take to school. Some of the respondents also reported that even though their children were home alone after school they were closely monitored by neighbours and relatives. Other parents reported that their children remained home alone without any form of supervision till either parent returned home, or were monitored by older siblings. While this social arrangement was not the preferred mode of raising children, a number of positive effects were attributed to it including learning to be independent and responsible, self reliance and competence in household chores for girls.